2021
DOI: 10.1080/00221686.2020.1870007
|View full text |Cite|
|
Sign up to set email alerts
|

Free-surface behaviour of shallow turbulent flows

Abstract: Over the last two decades, interest in the free-surface behaviour of gravity-driven shallow turbulent flows has increased considerably. It is believed that observation of free-surface behaviour can provide useful information about the hydrodynamic characteristics of the flow and enable remote retrieval of these characteristics to non-invasively and rapidly monitor river flows. At the current state the literature presents scattered knowledge and also exhibits non-uniformity in the terminology used. This paper i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 80 publications
0
17
0
Order By: Relevance
“…Our data (Figures 7 and 8) suggest we see this blindness, with nearly identical data paths from the taller REs (Figure 14). We see kinks in the data when the flow reaches the point where it encounters the top of The free-surface is the dynamic and turbulent surface of the rivers' flow, and therefore is affected by flow disturbing REs (Muraro et al, 2021). Flammer et al (1970) observed that as relative submergence increased, the flow transitions between three phases of pronounced, gradual and negligible free-surface effects.…”
Section: Re Impact On Sub-aerial Soundmentioning
confidence: 85%
See 1 more Smart Citation
“…Our data (Figures 7 and 8) suggest we see this blindness, with nearly identical data paths from the taller REs (Figure 14). We see kinks in the data when the flow reaches the point where it encounters the top of The free-surface is the dynamic and turbulent surface of the rivers' flow, and therefore is affected by flow disturbing REs (Muraro et al, 2021). Flammer et al (1970) observed that as relative submergence increased, the flow transitions between three phases of pronounced, gradual and negligible free-surface effects.…”
Section: Re Impact On Sub-aerial Soundmentioning
confidence: 85%
“…The free‐surface is the dynamic and turbulent surface of the rivers' flow, and therefore is affected by flow disturbing REs (Muraro et al., 2021). Flammer et al.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a growing interest by the scientific community, the research on the interaction between a turbulent flow and its free surface is still a relatively young and largely unexplored topic (Muraro et al., 2021). This work has confirmed the existence of a link between the water surface dynamics and macroscopic flow parameters such as surface velocity and water depth at a field scale, and has demonstrated the potential to monitor river discharge entirely remotely, with a physics‐based approach.…”
Section: Discussionmentioning
confidence: 99%
“…All waves with ω = 0 are stationary waves. Among these, the stationary waves with the crest perpendicular to the flow (k 2 = 0) are of importance because they define the representative scale of water surface deformations for turbulent flows over rough beds in the laboratory and in the field (Dolcetti & García Nava, 2019b;Dolcetti et al, 2016;Muraro et al, 2021). The wavenumber of these stationary waves, k 0 , is found from the solution of Ω GW (k, U 0 , d) = 0 for a case with k 0 ⋅ U 0 = −k 0 U 0 , which results in…”
Section: Dispersion Relationsmentioning
confidence: 99%
See 1 more Smart Citation